Development of an unmanned vehicle - Goh, Khim Hui. (2010)
Security is very important in our homeland. Homeland without high security level would be exposed to harms and threats from dangerous organizations and people. Especially in our airport and tourist attractions, there are always large numbers of people passing through. Such crowds can be easily become the one of target for the terrorist and other form of crimes. Nowadays in our modern world, security is no longer only about techniques and methods. It also involves high technology equipments in order to achieve a higher level of defense. Technologies not only boost the efficiency of security but it also empowers us to become more responsive. In the older days, large numbers of security guards were to station at different places as sentries and patrol around areas as prowlers. Long working hours and bad weather would affect their efficiency and alertness. Hence, the purpose of this project is to design an autonomous vehicle to improve our security measures and systems for the changing security environment. Simple design concepts with mechanical principles are implemented on the autonomous vehicle to achieve the objectives. All parts and components like motors, controllers, encoder, linkages, suspensions and bearings are carefully selected during the development of the vehicle. The specification of the vehicle is designed according the needs of the user and environment. This vehicle will allow the user to monitor the situation of the environment either in the control room or driving on the vehicle itself. This vehicle is also designed for places like tourist attractions and institutions for the tourists and lecturers to travel from point to point conveniently.